Response to a Specific and Digitally Supported Training at Home for Students With Mathematical Difficulties - Re, Anna Maria; Benavides-Varela, Silvia; Pedron, Martina; De Gennaro, Maria Antonietta; Lucangeli, Daniela (Frontiers in Psychology, 2020)
The present study evaluated the effectiveness of a shortened, specialized and digitally supported training program for enhancing numerical skills in primary and secondary school children with Mathematical Difficulty. The participants (n = 57) were randomly assigned to two groups: for the experimental group the tasks were differentiated and adapted to each student’s learning profile and children of this group used a Web App i.e., “I bambini contano” for the improvement of arithmetic fact at home; for the control group the difficulty of the activities was graded according to the school curriculum, moreover this group did not use the Web App. Pre- to post-training measurements showed that children of the experimental group had an improvement significantly higher than the control group, in particular in arithmetic facts and written calculation. Moreover, a follow-up evaluation indicated that the efficacy of the experimental training program lasted up to two months after the intervention. The results indicate that a specialized face-to-face intervention along with a digitally supported training at home can benefit children with mathematical learning difficulties.